1999
DOI: 10.1074/jbc.274.36.25481
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Binds to Tau and Stimulates the Protein Kinase A-catalyzed Tau Phosphorylation of Serine Residues 262 and 356

Abstract: ␣-Synuclein has been implicated in the pathogenesis of several neurodegenerative disorders based on the direct linking of missense mutations in ␣-synuclein to autosomal dominant Parkinson's disease and its presence in Lewy-like lesions. To gain insight into ␣-synuclein functions, we have investigated whether it binds neuronal proteins and modulates their functional state. The microtubule-associated protein tau was identified as a ligand by ␣-synuclein affinity chromatography of human brain cytosol. Direct bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
296
3
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 354 publications
(320 citation statements)
references
References 46 publications
17
296
3
4
Order By: Relevance
“…In addition, we found that mimicking αS phosphorylation increased the number of inclusions per cell. NMR spectroscopy suggests that the enhanced aggregation is due to a direct binding of Rab8a to the C-terminus of αS that has been implicated in interactions with a variety of protein partners (Burre et al, 2010;De Genst et al, 2010;Jensen et al, 1999Jensen et al, , 2000Kawamata et al, 2001;Kim et al, 2002;Yap et al, 2011). Thus, our study provides a link between physiological αS interactions and pathogenic aggregation.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, we found that mimicking αS phosphorylation increased the number of inclusions per cell. NMR spectroscopy suggests that the enhanced aggregation is due to a direct binding of Rab8a to the C-terminus of αS that has been implicated in interactions with a variety of protein partners (Burre et al, 2010;De Genst et al, 2010;Jensen et al, 1999Jensen et al, , 2000Kawamata et al, 2001;Kim et al, 2002;Yap et al, 2011). Thus, our study provides a link between physiological αS interactions and pathogenic aggregation.…”
Section: Discussionmentioning
confidence: 78%
“…These data identify both PKA and GSK-3 as potential therapeutic targets for AD and other tauopathies that are characterized by neurofibrillary degeneration associated with the abnormal hyperphosphorylation of tau. It is interesting to note that 14-3-3 and ␣-synuclein, both of which stimulate PKA activity (61,62), are colocalized with neurofibrillary tangles in AD brain (63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, -synuclein, as a chaperone, has been reported to interact with many other proteins, including 14-3-3, ERK1/2, parkin, etc. [32][33][34][35][36][37] . However, some of these findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%